Whither Coronabonds? The Past and Future of the EMU in the Coronavirus Pandemic - Bodo Herzog (Intereconomics)
Abstract The long-term fiscal and economic damage of eurobonds in a rule-based fiscal architecture — as history corroborates — would be greater than the historical challenge of the coronavirus pandemic, unless there is a political union in Europe.